Substance use and psychosocial functioning of adolescents in Benue state, Nigeria: Assessing the role of age (2019)
Aim: To assess whether Substance Use (SU) is associated with Psychosocial Function (PF) among adolescent. Methods: Using a self-administered validated instrument, we obtained information on demographic, SU (defined as self reported affirmative use of one or more of any form of alcoholic drinks, cigarettes, hemps etc) and PF [using the adolescent psychosocial functioning inventory comprising of three subscales; optimism and coping strategies (OCS), behaviour and relationship problems (BRP) and general psychosocial dysfunction designed (GPD)] among 2272 apparently healthy adolescents. PF was categorized as ‘elevated’ if the psychosocial functioning index (PFI) score were >75th percentile, otherwise, ‘not elevated’ and multivariable-adjusted logistic regression was used to compute odds ratio (OR) and 95% confidence interval (CI) of SU for elevated PF risk. In addition, we applied Johnson Neyman (JN) technique to identifying the JN significance regions at which age moderated the SU-PF relationship at a statistical significance of two-sided P<0.05. Results: Prevalence of SU and elevated PF was 50.7% and 79.8% respectively. Prevalence of elevated PF differed insignificantly by sex, but the proportion of adolescent with elevated PFI on SU (82.6%) was significantly higher (P<0.001) compared to those with elevated PFI but not on SU (76.9%). Multivariable-adjusted odds of decreased OCS risk given SU exposure was; OR (95%CI): 1.3791 (1.1458-1.6698), P=0.0007. Similarly, multivariable-adjusted odds of elevated PF risk in the light of SU exposure was; OR (95%CI): 1.4286 (1.1617-1.7567), P=0.0007. Furthermore, the JN significance regions for moderated regression analyses of odds of decreased OCS risk was between 10.4years [OR (95%CI): 0.5820 (0.1411-1.0228), P=0.0097] and 16.7years [OR (95%CI): 0.3025 (0.0001-0.6050), P=0.0500]. Conclusion: Adolescents on SU are about one and half times at risk of psychosocial dysfunction and age significantly attenuated the SU-decreased OCS risk link particularly in early adolescence.